Relationship of Work Motivation with Nurse's Compliance in Identifying Patients on Drug Administration - Mappanganro, Andi; Munir, Nur Wahyuni; Yuliana, Andi; Mariyanti, Sri (An Idea Nursing Journal, 2024)
Nurses must have experience and knowledge in serving patients. One way to prevent potentially fatal errors, such as administering the wrong medication, drawing lousy blood, or medical procedures inappropriate to the patient's condition, is to identify the patient. This study aimed to determine the relationship between nurses' work motivation and compliance when identifying patients receiving medication. This research was designed observationally and used a cross-sectional approach. At the Faisal Islamic Hospital Makassar, 43 nurses were sampled. Nurse compliance observation sheets and work motivation questionnaires were used. The Chi-Square statistical test was used with a confidence level of ? = 0.05. The results showed that, with a value of p = 0.035, there was a relationship between nurses' work motivation and their compliance in identifying patients when administering medication. The recommendation from this research is that the head of the room must carry out regular supervision regarding nurses' compliance in administering medication according to standard hospital operational procedures.